Tinjauan Hukum Islam Tentang Indomaret Card Di Indomaret Grogol Sukoharjo Jawa Tengah - Aslamiyah, Aslamiyah; , Dr.M. Muhtarom,SH, MH (2016)
A trading should be conducted by obeying requirements and pillars determined by Islamic Law. It aims to keep goods and their pricings are in line with general. Thus, if a good has some flaw, consumer must know it. It is needed to ensure and provide protection for consumers. Another case happens in Indomart of Grogol, Sukoharjo, Central Java. The department store uses mechanism of member card in which an owner of the card gets discount. The discount is not applied for non-owner. Problem statement of the research is: How does Islamic Law see the use of Indomaret card for transaction in Indomaret of Grogol, Sukoharjo, Central Java? The research is qualitative one. Data is collected by using observation, interview and documentation. The data is analyzed by using descriptive normative analysis. Based on results of the research, it is known that Islamic Law states that principle of a trading transaction is an agreement or wiliness between two parties, namely a seller and a buyer and, there is no element of force coming from both related parties and, the sold goods are useful for consumer. There is no element that are forbidden according to Islamic Law in transaction using member card in the Indomart. Therefore, the use of member card (Indomaret Card) for transaction in Indomaret of Grogol, Sukoharjo, Central Java is permitted or valid according to Islamic law. Key words: Islamic Law, Indomaret Card, Indomart